Surgical excision of BioZorb device eroding through the nipple‐areolar complex one year postoperatively: A case report. Issue 3 (25th January 2021) - Ju, Tammy; Tsai, Jacqueline
Abstract: The recent use of placing a BioZorb device during breast conservation surgery has been shown to improve targeting of adjuvant radiation therapy by significantly reducing target volume to the breast. However, the risks of surgical and/or infectious complications related to a BioZorb placement are largely unknown. In this case report, we describe a patient who underwent BioZorb placement after breast lumpectomy for ductal carcinoma in situ (DCIS), who presented with repeated infections and eventual erosion of the BioZorb through her nipple‐areolar complex (NAC), requiring surgical debridement and excision of her NAC and BioZorb 1 year postoperatively.